PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS KONSTRUKTIVISME PADA MATERI MATRIKS DI KELAS XI SMA NEGERI 7 PADANG - TRISNA DAMAYANTI (Departemen Matematika, 2021)
Interactive learning media is a supporting tool in the learning process to make it more interesting. Interactive media is very helpful for students in understanding learning material and developing students' critical thinking skills. This study aims to develop constructivism-based interactive learning media on matrix material in class XI SMA Negeri 7 Padang which is valid and practical. The type of research used is a Plomp model development research which consists of three stages, namely the preliminary stage, the making of the prototype and the assessment stage. Based on the validation results obtained on the aspects of the feasibility of content, language and media for constructivism-based interactive learning media has a validity level of valid category. Based on the practicality results obtained from trials with three students to use constructivism-based interactive learning media, it has a practicality level of very practical category. The overall results of the study indicate that constructivism-based interactive learning media are valid and practical. Keywords – Interactive Learning Media, Constructivism, Plomp